Does Emotional Intelligence Prevent Workplace Bullying? A Research on Sports Institution Employees - Tuncay Öcal,; İbrahim Şahin,; Nuriye Şeyma Kara,; Merve Nur Yaşar,; Serkan Necati Metin, (Journal of Educational Issues, 2024)
This study aimed to investigate the relationship between emotional intelligence and workplace bullying in the Provincial Directorate of Youth Services and Sports. 309 (215 men, 94 women) Sports Provincial Directorate of Youth Services staff from seven different cities of Turkey participated as volunteers in the research. In the study, the personal information form prepared by the researcher, the “Wong and Law Emotional Intelligence Scale” developed by Wong and Law (2002) and adapted to Turkish by Deniz (2012) were used. To determine the workplace bullying level, 21-question “Negative Behaviors Scale” developed by Einarsen (1996) and adapted to Turkish by Cemaloglu (2007) was used. A statistically significant difference was found between the groups according to the emotional intelligence level in the sub-dimension of evaluation of others’ emotions in terms of gender variables. No statistically significant difference was determined between the groups according to the gender variable in terms of workplace bullying. A statistically significant difference was found between the groups in terms of the duration of work, according to emotional intelligence levels and workplace bullying. When the relationship between emotional intelligence and workplace bullying was examined, it was found that there were negative significant correlations in some sub-dimensions. As the level of emotional intelligence of the employees increased, the cases of exposure to bullying decreased.